Infrared Thermography in Detecting Peripheral Arterial Disease in Diabetic Foot: A Scoping Review - Ken Rangga Galang Adiantara; Heri Kristianto; Yuyun Yueniwati (Jurnal Health Sains, 2024)
Early and accurate assessment of peripheral arterial disease (PAD) is crucial given its fatal complications such as amputation. Infrared thermography (IRT) offers various advantages in studying PAD. This study aims to map the use of Infrared thermography in detecting Peripheral Arterial Disease in diabetic feet. This review applies the scoping review method to review the literature related to Infrared thermography in detecting vascular disorders in diabetic legs. Article searches are conducted on five databases, namely Google Scholar, PubMed, EBSCO, ScienceDirect, and ProQuest. The Boolean keywords and codes used are "Infrared Thermography" AND "Diabetic foot" AND "Peripheral Arterial Disease". Searches are limited to articles published between 2018 and 2024. The journal selection process follows PRISMA's guidelines. The search process yielded 1,969 article titles relevant to the keywords and Boolean operators used. After being selected based on the research topic, 8 articles were left for analysis. IRT can be a useful tool for detecting PAD in diabetic foot. IRT can help track the progression of PAD and classify the foot as PAD without or prone with high accuracy